Function and expression of CD1d and invariant natural killer T‐cell receptor in the cotton rat (Sigmodon hispidus). Issue 4 (14th October 2015) - Fichtner, Alina Suzann; Paletta, Daniel; Starick, Lisa; Schumann, Richard F.; Niewiesk, Stefan; Herrmann, Thomas
Summary: The cotton rat ( Sigmodon hispidus ) belongs to the rodent family of Cricetidae and provides a powerful model to study the pathogenesis of human respiratory viruses and measles virus. Recent studies in other rodent models have suggested a role for invariant natural killer T (iNKT) cells in antiviral immunity and vaccination against respiratory virus infections. Using new experimental tools, we provide the first evidence for a functional CD1d cell molecule (crCD1d) and iNKT T‐cell receptor in cotton rats. The crCD1d cDNA sequence was identified and crCD1d transductants showed that monoclonal antibody WTH‐2 stains crCD1d as efficiently as mouse or rat CD1d. The expression of crCD1d was clearly weaker for thymocytes and B cells, and higher for T cells, which is different to what is found in murine species. The antigen‐presenting capacity of crCD1d was demonstrated with crCD1d–immunoglobulin dimers loaded with the glycolipid PBS57, which bound iNKT T‐cell receptors. Evidence for functional cotton rat iNKT cells was provided by detection of interferon‐ γ and interleukin‐4 in cultures of splenocytes stimulated with PBS57 and α‐galactosylceramide and by specific staining of about 0·2% of splenocytes with PBS57‐loaded crCD1d dimers. Canonical AV14/AJ18 rearrangements were identified and found to contain multiple members of the AV14 ( AV11 ) family. One of them was expressed and found to bind CD1d dimers. In summary, these data provide the first evidence for functional CD1d molecules and iNKT T‐cell receptors in cotton rats and provide the tools to analyse them both in the cotton rat model of infectious diseases.